2016
DOI: 10.4081/jphr.2016.768
|View full text |Cite
|
Sign up to set email alerts
|

Are Food Labels Effective as a Means of Health Prevention?

Abstract: Chronic diseases related to unbalanced and unhealthy eating habits have definitely become one of the major issues of modern age, not only in western countries but also in those ones where rapid economic growth has increased global prosperity levels. In order to avoid medical systems to collapse under excessive costs, International and Public Organizations strongly support health policies that aim to make people shift towards wholesome dietary patterns, also encouraging the use of food-labels to choose healthie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 29 publications
1
33
0
2
Order By: Relevance
“…If food labels can greatly influence the public health, its rates of use should be increased among Koreans. A previous study suggested that food labels can effectively be used as a means of health prevention and the awareness of food label usefulness among all consumers should be raised [15]. A systematic review and meta-analysis findings suggested that nutrition labelling may be an effective approach to empowering consumers in choosing healthier products [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If food labels can greatly influence the public health, its rates of use should be increased among Koreans. A previous study suggested that food labels can effectively be used as a means of health prevention and the awareness of food label usefulness among all consumers should be raised [15]. A systematic review and meta-analysis findings suggested that nutrition labelling may be an effective approach to empowering consumers in choosing healthier products [16].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the prevention and management strategy of obesity should be to reinforce consumers' perception and use of nutrition labeling of foods [8]. Previous studies have investigated the predictors, strategies, impacts, and effectiveness on nutrition label use [7,8,[11][12][13][14][15][16][17][18][19][20][21]. Studies on the factors associating nutrition labeling and obesity are limited.…”
Section: Introductionmentioning
confidence: 99%
“…FDA-regulated product labels are considered an important tool for protecting consumers and enabling informed decision-making. 11 Widespread mislabeling of hemp and Cannabis products has been documented by both independent researchers and the FDA and other organizations. 12,13 Underlabeling and overlabeling of both CBD and THC content have been reported.…”
Section: What's In a Label?mentioning
confidence: 99%
“…Nutrition means a behavior for the purposes that; protection of health, growing and development, increasing of life quality and required for the body using sufficient levels of nutritional components by accurate timing and consciously (Viola et al, 2016). Human being provides the nutritional needs of animal and plant based food sources.…”
Section: Intrоduсtiоnmentioning
confidence: 99%